Awareness, Access and Use of Locally Published Journals among Researchers in the Tanzanian Universities - Wema, Evans F; Ndumbaro, Faraja (University of Dar es Salaam Library Journal, 2017)
This is a baseline study of researchers ' awareness, access and use of locally published academic journals. Specifically the study addressed the following research questions: to what extent researchers in Tanzanian public universities awareness of the available indexed and non-indexed scholarly journals? What problems do researchers encounter when accessing local journals? And what are the researchers ' usage patterns of locally published journals? The study was conducted in five universities, which are: University of Dar es Salaam, Ardhi University, Sokoine universities of agriculture, Open University of Tanzania and Muhimbili University of health and allied sciences. The findings show that majority of researchers in higher learning institutions are aware of the available locally published journals within and outside areas of specialization. The findings further show that researchers, to large extent, use articles published from these journals to support their researches. Irregular publication of journals, lack of electronic versions for some journals and missing journal volumes and issues are among the factors that restrict access and use of local journals. It is recommended that for the journals to be published regularly, journal publishers with the support of their parent organizations should find ways of making them both sustainable and cost-effective, including adopting new models of journal publication. Libraries are also argued to improve the visibility of the journals by providing abstracting and indexing services.